Line intensities and temperature-dependent line broadening coefficients of Q-branch transitions in the v2 band of ammonia near 10.4 μm. (May 2016) - Sur, Ritobrata; Spearrin, R. Mitchell; Peng, Wen Y.; Strand, Christopher L.; Jeffries, Jay B.; Enns, Gregory M.; Hanson, Ronald K.
Abstract: We report measured line intensities and temperature-dependent broadening coefficients of NH3 with Ar, N2, O2, CO2, H2 O, and NH3 for nine sQ( J, K ) transitions in the ν2 fundamental band in the frequency range 961.5–967.5 cm −1 . This spectral region was chosen due to the strong NH3 absorption strength and lack of spectral interference from H2 O and CO2 for laser-based sensing applications. Spectroscopic parameters were determined by multi-line fitting using Voigt lineshapes of absorption spectra measured with two quantum cascade lasers in thermodynamically-controlled optical cells. The temperature dependence of broadening was measured over a range of temperatures between 300 and 600 K. These measurements aid the development of mid-infrared NH3 sensors for a broad range of gas mixtures and at elevated temperatures. Highlights: Spectroscopy of nine ammonia transitions in the Q-branch of ν2 band. High resolution spectroscopy performed with quantum cascade lasers (QCLs). Line intensities were measured using pure ammonia at room temperature. Collision broadening coefficients measured with Ar, N2, O2, CO2, H2 O, and NH3 . Temperature-dependence of broadening coefficients were measured up to 600 K.